Calcium Propionate and Feather Meal as Glucogenic Precursors in Lactating Saanen Goats - Serrato-Corona, J. Santos; Quiroz, Isauraivon RamÃrez (Indian Journal of Animal Nutrition, 2017)
An experiment was conducted to evaluate the effect of propionate and feather meal on milk production and milk chemical composition in goats in mid-lactation. Eighteen Saanen goats with an average body weight of 54.8Â±7.1 kg were were randomly assigned to three treatments having 6 animals each. Goats in the CON groupreceived the control diet plus 40 mL of sugarcane molasses but no glycogenic precursors. Goats in the CAPS group received the control diet plus 15 g of salts of calcium propionate dissolved in 40 mL of sugarcane molasses per goat daily while goats in the FEME group received the control diet plus 106 g of feather meal dissolved in 40 mL of sugarcane molasses. Milk production was higher (P